2012
DOI: 10.1371/annotation/48f605ab-75a9-4f93-9b4a-ab4358cd15d6
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Potential Role of Specific Antibodies as Important Vaccine Induced Protective Mechanism against Aeromonas salmonicida in Rainbow Trout

Abstract: Furunculosis caused by infection with Aeromonas salmonicida subsp. salmonicida has been a known threat to aquaculture for more than a century. Efficient prophylactic approaches against this disease are essential for continued growth of salmonid aquaculture. Since the introduction of successful oil-adjuvanted vaccines in the early 1990's, a number of studies have been published on the protective as well as adverse effects of these vaccines. Most studies focus on vaccination of salmon (Salmo salar). However, rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…IgM titers were noticeably higher in the OMVs boosted animal at 14 days following ip challenge ( Figure 10 B). Villumsen et al (2012) reported that the experimental vaccine produced noticeably greater IgM titers in each of the three intervals between immunization and challenge compared to the unvaccinated controls [ 81 ], which is similar to our results ( Figure 6 and Figure 10 B).…”
Section: Discussionsupporting
confidence: 91%
“…IgM titers were noticeably higher in the OMVs boosted animal at 14 days following ip challenge ( Figure 10 B). Villumsen et al (2012) reported that the experimental vaccine produced noticeably greater IgM titers in each of the three intervals between immunization and challenge compared to the unvaccinated controls [ 81 ], which is similar to our results ( Figure 6 and Figure 10 B).…”
Section: Discussionsupporting
confidence: 91%